Formation of biofilm on different particulate media using modified kitchen waste extract as initial growth substrate for use in PCB degradation - Auresenia, Joseph L. (Animo Repository, 2005)
This study describes the formation of biofilm on two different particulate media using modified kitchen waste extract as initial growth medium, and the subsequent testing of the this biofilm to biodegrade polychlorinated biphenyls (PCBs). Two parallel completely mixed fluidized bed reactors, one using cement balls and the other using sand as particulate media, were operated in order to produce the biofilm. Modified kitchen waste extract was used as a growth substrate instead of the more expensive complex substrate. The medium was inoculated with microorganisms from tannery wastes. Performance of the biofilms formed in the two reactors were compared based on BOD and COD degradation rates, biomass growth rate, biofilm thickness and ease of fluidization. The results demonstrate that a stable biofilm can be formed on readily available particulate materials using cheap substrate from kitchen wastes extracts. Furthermore, cement balls proved to be more suitable as particulate media compared to sand, possessing superior biofilm-forming characteristics. The biofilm formed on cement balls was tested for the degradation of PCBs. Initial PCB batch degradation tests showed that about 70% of PCBs degraded within six hours. Kinetics of PCB degradation followed the Monod model with Km = 561.98 mg/l and μmax = 0.07 1/h.